Pengaruh Model Pembelajaran Problem Based Learning terhadap Kemampuan Berpikir Kritis Siswa SMP Negeri Halioan - Yovita Hoar; Stefania Sonia Manek; Wolfgang Asindo Seran (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Learning is the process of forming behavior or behaviorism and is seen from the cognitive aspect of students, in fact to support the achievement of ideal educational goals with the existing education system in Indonesia. In this research, the author is interested in researching students' cognitive aspects in line with 21st century learning to determine students' critical thinking abilities using the problem based learning model. This type of research is research using a quantitative research approach. The sample in this study was control class VII A students with a total of 13 students and VII B was an experiment with a total of 12 students at Halioam State Middle School, totaling 25 students. Data collection techniques use test questions and documentation, interviews. Data analysis used the independent sample t-test hypothesis test and the N-Gain score test. The results of the research show that the problem based learning model can have an influence on the critical thinking abilities of class VII students at Halioan State Middle School. This is proven by assessing students' critical thinking abilities using a hypothesis test using an independent sample t-test. The result was a 2-tailed sig of 0.000 < 0.05 so that there is an influence of the problem based learning model on Halioan State Middle School students' critical thinking abilitie.